Respuesta :
Answer:
Exponential function is of the form: [tex]y =ab^x[/tex]
where a is the initial value and b is the growth factor.
- If b> 1, then the function is exponential growth function.
- If 0<b<1, then the function is exponential decay function.
Given the parent function:
[tex]f(x)=y = (\frac{3}{2})^x[/tex] ....[1]
This function is an exponential growth function.
The rule of reflection over y-axis:
[tex](x, y) \rightarrow (-x, y)[/tex]
Apply the rule on f(x) we get;
[tex](\frac{3}{2})^{-x} = (\frac{2}{3})^x =g(x)[/tex]
Therefore, the function [tex]g(x) =(\frac{2}{3})^x[/tex] is the graph of the function f(x) reflected over y-axis.
The graph of the function g(x) is reflected over the y-axis to make the graph of the function f(x) and this can be determined by using the rules of transformation.
Given:
- [tex]f(x) = \left(\dfrac{3}{2}\right)^x[/tex]
- [tex]g(x) = \left(\dfrac{2}{3}\right)^x[/tex]
The following steps can be used in order to compare the graphs of the given function:
- Step 1 - Write the equations of the given exponential functions.
[tex]f(x) = \left(\dfrac{3}{2}\right)^x[/tex] --- (1)
[tex]g(x) = \left(\dfrac{2}{3}\right)^x[/tex] --- (2)
- Step 2 - Now, replace 'x' with '-x' in the expression (1).
[tex]f(-x) = \left(\dfrac{3}{2}\right)^{-x}[/tex]
- Step 3 - Simplify the above expression.
[tex]f(-x)=\left(\dfrac{2}{3}\right)^x[/tex]
[tex]f(-x)=g(x)[/tex]
- Step 4 - So, from the above steps, it can be concluded that the graph of the function g(x) is reflected over the y-axis to make the graph of the function f(x).
For more information, refer to the link given below:
https://brainly.com/question/13710437